Comparative luminescence study of LaBMoO6:Tb phosphor under VIS and Near-UV excitation for green photonic applications. (2018) - Kaewnum, E.; Wantana, N.; Kaewkhao, J.
Abstract: La(1-x) BMoO6 :Tbx phosphors were synthesis to study structure, absorption and luminescence properties. XRD results show monoclinic structure (P21 space group) LaBMoO6 host composition. This phosphor can absorb photon in near-UV, VIS and NIR region observed from reflectance spectra. VIS light with 487 nm and near-UV with 259 nm excitation resulted to strong green emission from Tb 3+ in phosphor. VIS excitation via 4f-f4 transition generated stronger emission than near-UV excitation via 4f-5d transition. From decay curve results, luminescence life time of phosphor is in millisecond order and energy transfer between Tb 3+ with dipole-dipole interaction was found in this under VIS excitation. The optimum composition of this phosphor for luminescence excited by VIS and near-UV is La0.96 BMoO6 :Tb0.04 and La0.84 BMoO6 :Tb0.16, respectively. La0.96 BMoO6 :Tb0.04 perform a good potential for using as green emitting powder in display and LED device, while La0.84 BMoO6 :Tb0.16 is suitable for applying in near-UV to VIS converter.